Mid-day Meal Programme and Adolescent Undernutrition- an Epidemiological Study in Hyderabad, India - Kodali, Prakash babu; Kopparty, Swarajya; Vallabhuni, Ramya; Kalapala, Gangadhar Rao (Journal of Pharmacy Practice and Community Medicine)
Background: Malnutrition is one of the most important public health challenges faced by the country. With more than 35% of its population in the productive age group being malnourished. Even though malnutrition in children and pregnant mothers are some of the most discussed topics in Indian public health, under nutrition among adolescents was not given much importance. In this article we try to look into the concept of under nutrition among adolescents and how government of India’s mid-day meal programme is able to influence it. Materials and Methods: Cross-sectional study design, sample was obtained by the means of multi-stage systemic random sampling, data was obtained from total sample size of 197 participants was obtained according to inclusion criteria, statistical techniques of correlation and Multivariate regression are used to analyze the results. Results: around 76.1% of the total participants are malnourished; malnutrition among adolescent boys is slightly higher than that of girls. Malnutrition among low economic status is higher than the students belonging to High income status. Correlation showed that age of the participants (Mean=14.37 years, and SD=1.05 years) and “BMI of the participants” (Mean=17.35 and SD=2.70) r= 0.174, p≤ 0.05, N=197, were significantly related with each other. Regression results yielded the influence of independent variables on BMI, for age b=0.497, t(197)=2.661, p≤0.01, for economic status b=0.225, t(197)=0.582, for gender b=-0.525, t(197)=-1.303. Conclusion: Around three quarters of the adolescents who were availing the midday meal scheme clearly show that midday meal scheme which is the sole source of essential protein and nutrients is not able to meet the need for the adolescents clearly showing need for the policy changes to be pitched in. behavior modification towards low-cost healthy diet, subsidies, and fortification of mid-day meal might be considered.
Keywords: Adolescent health; BMI; Health policy; Malnutrition; Mid-day Meal Programme